SMART Hygiene Kit / Dg Kamisah Ag Budin ... [et al.] - Ag Budin, Dg Kamisah; Andrew, Jasmine Vivienne; Mawardi, Faiqah; Mohamad, Mohammad Firdaus; Ag Damit, Dayang Haryani Diana (2021)
The new norm has pushed forward the practice of 3Ws (wash, wear, warn) introduced by the government to the public to prevent the further spread of COVID-19 (KKM, 2020). The COVID-19 virus spreads via droplets released when someone infected with the virus sneezes or coughs. Although there are various sources of information to educate the public about the importance of the 3W practice, there are still existing concerns on the improper wearing of face masks and hygiene practices. Thus, experts emphasize the importance of wearing face masks in public, proper personal hygiene, and disinfection practice to reduce the risk of virus infection. Many products related to COVID-19 protection, such as masks, sanitizers, and disinfectants, are sold in the market separately. It can be inconvenient, especially for having to carry many things at once. Therefore, a potential solution to reduce these worries is a new innovative product called 'SMART Hygiene kit', which combines the necessary mask protectors, hand sanitizer, and surface disinfectant. The interesting part is the compact size, and it comes in many colors which suit the preferences and personality of the users. The product is also equipped with a ring to hang it on their bag for the convenience of users. The novelty of this product is the convenience of bringing one product, 'SMART Hygiene kit', which provides all we need to prevent the spread of COVID-19. This innovation is useful for everyone by easing them to bring one product instead of getting all these necessities separately.